Development of the archive of the Moscow Theological Consistory in the first half of the 18th century - Ilya Ivanov (Вестник Православного Свято-Тихоновского гуманитарного университета: Серия ИИ. История, история Русской Православной Церкви)
Despite the wide popularity of the collection of the same name in the Central State Archive of Moscow, the archive of Moscow Theological Consistory is a unique and understudied phenomenon of the cultural heritage of the Russian Orthodox Church. The large documentary complex has for decades served as a breeding ground for research in a wide variety of fi elds of church-historical science. However, for almost two centuries, the formation of the archive itself, in contrast to genealogical research or the compilation of annals of individual churches, was almost out of focus of research attention. Meanwhile, the analysis of a wide range of documentary materials provides a much more accurate picture of the peculiarities of building an archive than the consideration of any private aspects of its functioning related to a particular group of documents. The establishment of the Consistory Archive in the fi rst half of the 18th century is seen as one of the least known events in its almost two-hundredyear existence. The reason for the emergence of many documents from its predecessor institutions and their future fate remains unknown. The 44th chapter of the General Regulations marked the beginning of the rapid growth of systematic archival work in the Russian Empire. The development of secular archives is much better aff ected in this respect than church archives. The documents in the MDK collection, despite their loss, provide an opportunity to study this process in detail in a church context. One of the most popular documentary complexes of its time is being developed in the consistory. The article, based on published and unpublished sources, attempts to reconstruct the early composition of documents, the infl uence of predecessor institutions on the grouping of material, the perception of the archive by the Consistorians, and the work of employees with the archive until the creation of the permanent position of archivist in 1749.